Death was the other woman [compact disc, unabridged] - Richards, Linda L, (Linda Lea), 1960- (Brilliance Audio, 2008)
Behind every great man - and even not-so-great - is a woman. For the shady Prohibition-era businessman Harry Dempsey, it's his mistress Rita. For the private eye she hires, Dexter Theroux, it's his secretary Kitty Pangborn. But Dexter's Prohibition-era problem (rotgut booze) forces Kitty to come out from behind him in order to keep the firm alive. Unfortunately, the enemies she makes on this case will do more than just kill business.